Type II and type IV toxin–antitoxin systems show different evolutionary patterns in the global Klebsiella pneumoniae population. Issue 8 (31st March 2020) - Horesh, Gal; Fino, Cinzia; Harms, Alexander; Dorman, Matthew J; Parts, Leopold; Gerdes, Kenn; Heinz, Eva; Thomson, Nicholas R
Abstract: The Klebsiella pneumoniae species complex includes important opportunistic pathogens which have become public health priorities linked to major hospital outbreaks and the recent emergence of multidrug-resistant hypervirulent strains. Bacterial virulence and the spread of multidrug resistance have previously been linked to toxin–antitoxin (TA) systems. TA systems encode a toxin that disrupts essential cellular processes, and a cognate antitoxin which counteracts this activity. Whilst associated with the maintenance of plasmids, they also act in bacterial immunity and antibiotic tolerance. However, the evolutionary dynamics and distribution of TA systems in clinical pathogens are not well understood. Here, we present a comprehensive survey and description of the diversity of TA systems in 259 clinically relevant genomes of K. pneumoniae . We show that TA systems are highly prevalent with a median of 20 loci per strain. Importantly, these toxins differ substantially in their distribution patterns and in their range of cognate antitoxins. Classification along these properties suggests different roles of TA systems and highlights the association and co-evolution of toxins and antitoxins.